Analisis Kemampuan Pemecahan Masalah Ditinjau dari Disposisi Matematis Siswa Sekolah Menengah Pertama pada Mata Pelajaran Matematika - Hertin, Hilda Hirmaliza; Sucipto, Lalu (Jurnal of Math Tadris, 2024)
This research aims to analyze problem solving abilities in terms of students' mathematical disposition in class VIII mathematics subjects at Darul Hikmah Karang Genteng Middle School, Pagutan. This type of research is qualitative with descriptive methods. The research subjects were 18 class VIII students. Data on problem solving abilities was collected through interviews with 2 students with a high mathematical disposition, 2 students with a medium mathematical disposition and 2 students with a low mathematical disposition. The result is the mathematical disposition of class VIII students at Darul Hikmah Middle School is divided into three categories, namely high, medium and low. Students with a high mathematical disposition have high problem solving abilities because they are able to fulfill the four indicators of problem solving according to Polya's theory, namely, understanding the problem, planning a solution, resolving the problem and checking again. Students with a moderate mathematical disposition have moderate problem solving abilities because they fulfill the three indicators of problem solving according to Polya's theory, namely, understanding the problem, solving the problem and checking again. And students with a low mathematical disposition have low problem solving abilities because they only fulfill two indicators of problem solving according to Polya's theory